2013
DOI: 10.1038/pr.2013.87
|View full text |Cite
|
Sign up to set email alerts
|

Does insulin-like growth factor-1 mediate protein-induced kidney growth in infants?: A secondary analysis from a randomized controlled trial

Abstract: Background: Animal models have shown that insulin-like growth factor I (IGF-I) may mediate protein-induced kidney growth. Our aim was to analyze the effect of IGF-I on proteininduced kidney growth in healthy infants. Methods: This is a secondary analysis of a randomized trial that compared growth of infants fed with a higher-protein (HP) (n = 169) vs. lower-protein (LP) (n = 182) formula (in the first year of life). Outcome measures were anthropometric parameters, kidney volume (cm 3 ), and total and free IGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
(37 reference statements)
1
13
0
Order By: Relevance
“…These findings in adults were also observed in younger patients as well as in animal models (14)(15)(16). Recently, we found that nonextremely variations in protein supply with infant formulae resulted in varying kidney growth and function in healthy infants, and this was partly mediated by modulation of the IGF-1 axis (3,7).…”
supporting
confidence: 59%
See 3 more Smart Citations
“…These findings in adults were also observed in younger patients as well as in animal models (14)(15)(16). Recently, we found that nonextremely variations in protein supply with infant formulae resulted in varying kidney growth and function in healthy infants, and this was partly mediated by modulation of the IGF-1 axis (3,7).…”
supporting
confidence: 59%
“…This mechanism is partly responsible for the protein-induced increase in anthropometric parameters, as well as in some internal organs such as the kidney in healthy children (7,29). Protein intake induces IGF-1 secretion which, in turn, induces an increase in weight through its anabolic and metabolic effects in most cell lines (30,31).…”
Section: Role Of the Igf-1 Axismentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, IGF-I concentrations have been associated with weight gain in the first 6 months of life [7]. Additionally IGF-I could partly mediate protein-induced kidney growth in healthy children [8]. This phenomenon was observed in the HP group: children at 6 months of life showed a significantly greater kidney volume compared with the LP group [9].…”
mentioning
confidence: 99%